Diversifying the structural architecture of synthetic oligomers: the hetero foldamer approach - Roy, Arup; Prabhakaran, Panchami; Baruah, Pranjal Kumar; Sanjayan, Gangadhar J. (Chemical Communications, 2011)
Conformationally ordered synthetic oligomers, also called ``foldamers'', have attracted considerable attention in recent years owing to their ability to mimic the structural architecture of biopolymers and also because of their potential applications in biomedical and material science fields. Until recently, the major focus in this area has been the development of oligomers featuring a single type of monomer building blocks. However, due to the enormous possibility of augmenting the conformational space available for oligomer design, the hetero foldamer approach has been introduced very recently. This feature article aims to describe foldamers with unique structural architectures, exclusively featuring heterogeneous backbones (hetero foldamers).